Activities of metabolizing enzymes in human placenta. (15th June 2020) - Mohammed, Ali Mustafa; Huuskonen, Pasi; Juvonen, Risto; Sahlman, Heidi; Repo, Jenni; Myöhänen, Kirsi; Myllynen, Päivi; Woo, Chit-Shing Jackson; Karttunen, Vesa; Vähäkangas, Kirsi
Highlights: CYP19A1, UGT, GST and CAT activities were confirmed in human placenta. High interindividual variation was found in the enzyme activities. Several chemicals affected the enzyme activities in human placental perfusion Antipyrine in placental perfusion may alter the activities of the analyzed enzymes. Abstract: In addition to the transfer across the placenta, placenta displays hormonal and xenobiotic metabolism, as well as enzymatic defense against oxidative stress. We analyzed aromatase (CYP19A1), uridine 5′-diphospho-glucuronyltransferase (UGT), glutathione-S-transferase (GST) and catalase (CAT) activities in over 70 placentas from nonsmokers stored at -80 °C from former perfusion studies. A wide interindividual variation in all activities was found. Longterm storage at -80 °C did not affect the activities. Ethoxyresorufin-O-deethylase (EROD, CYP1A1) was not detected in any of the studied placentas perfused with chemicals. Several compounds in placental perfusion changed statistically significantly the enzyme activities in placental tissue. Melamine and nicotine increased CYP19A1, melamine increased UGT and GST, PhIP with ethanol decreased CYP19A1 and increased GST, and PhIP with buprenorphine decreased CAT. Antipyrine in 100 μg/ml also changed the studied enzyme activities, but not statistically significantly. Because antipyrine is a reference compound in placental perfusions, its potential effects must be taken into account in human placental perfusion. Enzyme activities deserve further studies as biomarkers of placental toxicity. Finally, enzyme activities deserve further studies as biomarkers of placental toxicity.